Spill The Tea: Fenomena Gibah Masa Kini Perspektif Alquran (Kajian Tafsir Maudhu’i) - Raihan Raihan; Muhammad Reza Fadhil; Esya Heryana; Fitriani Fitriani; Winona Lutfiah (Jurnal Riset Agama, 2022)
This study aims to examine the phenomenon of spill the tea which is included in the gibah category and is widely practiced by social media users. So this research is crucial to be discussed. The method used in this study is a type of qualitative research using library research, and also using the maudu'i interpretation method in discussing verses about the Koranic perspective gibah. The results and discussion of this show that there have been many verses of the Qur'an that have indicated the prohibition to commit backbiting and the consequences that arise from these actions. Through this research, a common thread can be drawn that backbiting can trigger the emergence of various serious problems such as hostility, mutual hatred and revenge, depression and even very dangerous if it leads to murder or suicide. However, sadly in today's era, the behavior of backbiting is increasingly being underestimated. So responding to the dangers of this backbiting action, of course, scientific studies about backbiting are needed to be able to sterilize the situation and provide positive energy so that it can minimize the rampant phenomenon of backbiting today, both in the real world and in cyberspace.